Transversalização de gênero no Plano Nacional de Políticas para as Mulheres: desafios estruturais para a implementação de metas e o ativismo das trabalhadoras domésticas - Barbosa, Marina Rongo (2021)
This work will study the implementation of gender mainstreaming in Brazil through the analysis of the Third National Plan for Women's Policy (PNPM) of 2013, specifically to identify the achievement of its goals aimed at expanding the labor rights of domestic workers, as well as other engagement strategies with the State in this category. The hypothesis that we intend to prove is that the activism and political influence of domestic workers in Brazil challenges the dichotomy present in the feminist literature on gender mainstreaming, with regard to transformation / non-transformation, which will be supported here mainly by opposing theories of Squires and Prügl. Therefore, in the first chapter the concept of gender mainstreaming will be discussed in greater depth, explaining its origins, historical path, differences in relation to other gender equality strategies and their different approaches. In the second chapter, an analysis will be presented, through secondary sources, on the process of construction of National Plans for Women's Policies in National Conferences on Women's Policies, in order to identify whether there was the adoption of deliberative practices in such events. Then, it will be debated whether it is also possible to identify state declarations concurrently with the demands for rights of domestic workers. Finally, in the third and last chapter, texts and arguments will be gathered to demonstrate that the activism of domestic workers challenges the logic of mainstream feminism on the possibility of having or not transformation based on social engagement with the State. This paper concludes that it seems that Gender mainstreaming comes from the social movement to the State and from within with its empowerment practices. Thus, the case of domestic workers seems to demonstrate that there is an escape from the dichotomy that mainstreaming theorists present to us, allowing for a middle way, which is paradoxical, but through which we can see the transformation coming from below gradually